Trunk performance after stroke: an eye catching predictor of functional outcome. Issue 7 (18th December 2006) - Verheyden, Geert; Nieuwboer, Alice; De Wit, Liesbet; Feys, Hilde; Schuback, Birgit; Baert, Ilse; Jenni, Walter; Schupp, Wilfried; Thijs, Vincent; De Weerdt, Willy
Abstract : Background and aim: Trunk performance is an important predictor of functional outcome after stroke. However, the percentage of explained variance varies considerably between studies. This may be explained by the stroke population examined, the different scales used to assess trunk performance and the time points used to measure outcome. The aim of this multicentre study was to examine the predictive validity of the Trunk Impairment Scale (TIS) and its subscales when predicting the Barthel Index score at 6 months after stroke. Methods: A total of 102 subjects were recruited in three European rehabilitation centres. Participants were assessed on admission (median time since stroke onset 20 days) and 6 months after stroke. Correlation analysis and forward stepwise multiple regression analysis were used to model outcome. Results: The best predictors of the Barthel Index scores at 6 months after stroke were total TIS score (partial R 2  = 0.52, p<.0001) and static sitting balance subscale score (partial R 2  = 0.50, p<.0001) on admission. The TIS score on admission and its static sitting balance subscale were stronger predictors of the Barthel Index score at 6 months than the Barthel Index score itself on admission. Conclusions: This study emphasises the importance of trunk performance, especially static sitting balance, when predicting functional outcome after stroke. The TIS is recommended as a prediction instrument in the rehabilitation setting when considering the prognosis of stroke patients. Future studies should address the evolution of trunk performance over time and the evaluation of treatment interventions to improve trunk performance.